Analisis Hubungan Pengetahuan, Sikap, Motivasi, Dukungan Keluarga dan Peran Tenaga Kesehatan dengan Keberhasilan Melakukan Teknik Sadari pada WUS di Puskesmas Pakuan Baru Kota Jambi Tahun 2019 - Laida Sanilpa Tiwi (Universitas Batanghari Jambi, 2023)
BSE (Breast Self Examination) is an examination which is easily done by every woman to look for lumps or other abnormalities. The factors that govern the behavior of the successful conduct BSE technique is the knowledge, attitudes, motivation, family support and the role of health professionals. The purpose of this study was to determine the relation of knowledge, attitude, motivation, family support and the role of health workers with the successful conduct of BSE technique in women of reproductive age (WUS). This research uses survey method with cross sectional analytic. This study population is women of childbearing age (WUS), amounting to 3,663 person sample were 96 people by means of quota sampling. Data collection techniques in this study using primary data with a questionnaire. Data were analyzed using chi-square statistical test. The results of the study there is a significant relationship between knowledge (p-value = 0.005), family support (p-value = 0.000), the role of health workers (p-value = 0.000) and no significant relationship between attitude (p-value = 1.00) and motivation (p-value = 0.140) with the successful conduct breast self-examination technique. For logistic regression statistical tests are the most dominant variable influence on the success of doing teknik SADARI in women of reproductive age (WUS) is the variable role of health workers with a p-value = 0.000 (OR : 10,490). The conclusion of this study are variables simultaneously the role of health workers with family support variables affect the success of techniques BSE.Â